2016
DOI: 10.3109/09687637.2015.1136265
|View full text |Cite
|
Sign up to set email alerts
|

Exploring prison drug use in the context of prison-based drug rehabilitation

Abstract: Aims: The research on motivations and meanings associated with drug use in prisons has received little scholarly attention. Particularly, there are few studies analysing drug use in prisons from the perspective of both prisoners and prison officers, and in the context of prisonbased drug rehabilitation. This article explores prisoners and prison staffs perceptions on why drug use occurs in prison. Methods: The data is derived from participant observation and qualitative interviews (N ¼ 35) conducted during eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…by being able to bring drugs into prisons, making connections to outside drug and criminal networks, and displaying courage) and the feeling among prisoners that they are part of a larger social network. This is also in line with Mjåland's (2016) findings in this Issue. Similarly, he found that prisoners who distributed and also shared drugs could earn respect.…”
supporting
confidence: 82%
“…by being able to bring drugs into prisons, making connections to outside drug and criminal networks, and displaying courage) and the feeling among prisoners that they are part of a larger social network. This is also in line with Mjåland's (2016) findings in this Issue. Similarly, he found that prisoners who distributed and also shared drugs could earn respect.…”
supporting
confidence: 82%
“…As such, they would need to adapt, often meaning that inmates would have to hide drugs within body cavities. One inmate reported that it was no secret that everyone brought drugs into prison using the plug approach [6,21,27]. In January 2015, custody staff found 20 ecstasy tablets in the waistband of tracksuit bottoms, bags of cannabis sewn into the lining of underwear and in the trainers of a man convicted with firearms offences [15].…”
Section: New or Returning Prisonersmentioning
confidence: 99%
“…When locked in their cells, inmates create makeshift ropes known as 'lines' to pass drugs between cell windows [16]. Prisoners also divert legally prescribed medication, they sip the medication in front of the nurse and will later spit it out into a cup to give or sell to other inmates [16,27].…”
Section: New or Returning Prisonersmentioning
confidence: 99%
“…Resultatene viste at det var en sterk norm blant innsatte om å holde rusbruk skjult for ansatte både på Venterommet og Slusa, noe som samsvarer med funn i andre fengselsstudier (Mjåland 2016). Innsatte ved Kollektivet oppga derimot at de tok opp og diskuterte rusbruk under oppholdet i gruppene.…”
Section: Diskusjonunclassified